2023
DOI: 10.2967/jnumed.122.265247
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of TSPO PET Before Radiotherapy in Newly Diagnosed IDH–Wild-Type Glioblastoma

Abstract: The 18-kDa translocator protein (TSPO) is gaining recognition as a relevant target in glioblastoma imaging. However, data on the potential prognostic value of TSPO PET imaging in glioblastoma are lacking. Therefore, we investigated the association of TSPO PET imaging results with survival outcome in a homogeneous cohort of glioblastoma patients. Methods: Patients were included who had newly diagnosed, histologically confirmed isocitrate dehydrogenase (IDH)-wild-type glioblastoma with available TSPO PET before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3E ), also after adjustment for age, sex, the TSPO SNP and initiation of glucocorticoid medication prior to PET as covariates (F 1,25 = 7.01, p = 0.014). Testing previously evaluated parameters and indices (22) ( Supplemental Table 1 ), a significant impact on survival in the current cohort was identified by univariate Cox regression for age (HR: 1.06, p = 0.015), subsequent radiotherapy (HR: 0.27, p = 0.024) and chemotherapy (HR: 0.31, p = 0.003) as well as TSPO-PET signal of the tumor (HR: 1.85, p = 0.024), T1 contrast enhanced volumes (HR: 1.03, p < 0.001) and T2 hyperintensity volumes (HR: 1.02, p < 0.001). Furthermore, high contralateral TSPO-PET signal was associated with shorter survival in univariate Cox regression (HR: 1.72, p < 0.001; Log-rank test after median split: Χ² = 4.22, p = 0.040, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3E ), also after adjustment for age, sex, the TSPO SNP and initiation of glucocorticoid medication prior to PET as covariates (F 1,25 = 7.01, p = 0.014). Testing previously evaluated parameters and indices (22) ( Supplemental Table 1 ), a significant impact on survival in the current cohort was identified by univariate Cox regression for age (HR: 1.06, p = 0.015), subsequent radiotherapy (HR: 0.27, p = 0.024) and chemotherapy (HR: 0.31, p = 0.003) as well as TSPO-PET signal of the tumor (HR: 1.85, p = 0.024), T1 contrast enhanced volumes (HR: 1.03, p < 0.001) and T2 hyperintensity volumes (HR: 1.02, p < 0.001). Furthermore, high contralateral TSPO-PET signal was associated with shorter survival in univariate Cox regression (HR: 1.72, p < 0.001; Log-rank test after median split: Χ² = 4.22, p = 0.040, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3F ). We proceeded with a multivariate Cox regression model including significant indices as well as MGMT, which likely did not reach significance in univariate Cox regression due to the lower sample size compared to a previous study (22), and glucocorticoid medication due to borderline significance. Here, high contralateral TSPO-PET signal was an independent predictor of shorter overall survival within the group of patients with glioblastoma (median OS: 6.5 vs 13.4 months, HR: 2.18, p = 0.005), together with age (HR: 1.12, p < 0.001), MGMT (HR: 0.20, p = 0.010), glucocorticoid medication (HR: 5.16, p = 0.011), and T1 contrast enhanced volume (HR: 1.04, p = 0.025; Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results highlight the value of static TSPO PET in predicting IDH mutation status, particularly in situations where dynamic [ 18 F]FET PET data have not been acquired. While TSPO PET is not intended to replace the well-understood and well-established [ 18 F]FET PET, its high performance has further been demonstrated in terms of survival prediction even among homogeneous molecular entities [ 25 , 26 ]. Consequently, it emerges as a vital supplementary non-invasive tool for optimizing early patient management at the point of initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from delineating active tumor, [ 18 F]FET PET has proven its utility in identifying intratumoral heterogeneity and differentiating tumor recurrence from pseudoprogression [20,21]. Despite being less tumor-specific, PET imaging using radioligands targeting the translocator protein (TSPO), which is upregulated not only in tumor cells but also in activated microglia or macrophages, has demonstrated correlations with histologic tumor grade, specific transcriptional glioma subtypes, and survival [22][23][24][25][26][27]. A recent study revealed that there is no correlation between PET information and relative contrast enhancement on T1-weighted MRI [28].…”
Section: Introductionmentioning
confidence: 99%